Antioxidant activity of Ruscus species from Serbia: Potential new sources of natural antioxidants - Jakovljević Violeta D.; Milićević Jasmina M.; Ðelić Gorica T.; Vrvić Miroslav M. (Hemijska Industrija, 2016)
The antioxidant activity, total phenolic and flavonoid content of ethanolic, acetone and ethyl acetate extracts of Ruscus hypoglossum L. and Ruscus aculeatus L. (aerial parts) from Serbia were investigated in this paper. The best total antioxidant capacity (23.329 μg AA g-1) and the highest DPPH scavenging activity (IC50 = 182.54 μg mL-1) were found in acetone and ethyl acetate extract of R. aculeatus L. Ethanolic extract of R. hypoglossum L. showed the highest ABTS radical cation scavenging activity (IC50 = 3.04 μg mL-1) as well as reducing power (IC50 = 0.143 μg mL-1). The best inhibitory activity against lipid peroxidation (IC50 =651 μg mL-1) and the best ferrous ion chelating ability (IC50 = 110 μg mL-1) were found in acetone and ethyl acetate extract of R. hypoglossum L. The highest total phenolic (8.569 mg GAE g-1) and flavonoid content (0.136 mg RU g-1) were found in ethanolic and acetone extract of R. hypoglossum L. and R. aculeatus L, respectively. [Projekat Ministarstva nauke Republike Srbije, br. III 43004]